Robert D. Kaplan, Asia’s Cauldron: The South China Sea and the End of a Stable Pacific - Mr. Gulandam Mian (CISS Insight Journal, 2015)
Robert D. Kaplan’s Asia’s Cauldron has made a timely appearance since over the last few years the world has concerned itself with the likely power shift from the West to Asia. His expert knowledge covers the regional and extra-regional powers and how they are hedging one another by strengthening relations with the littoral states that are focusing on updating their naval infrastructure. Most of the smaller states such as Philippines, Vietnam, and Thailand are looking up to the US for giving them security assurances against China. This in turn, is fueling military modernization of China. The situation is setting into motion Kenneth Waltz’s security dilemma in the region. All this according to the author’s analysis are enough to make it a “cauldron” on high flame and a region of future conflict. The author’s comparative analysis of the 21st century conflict in the South China Sea with the European conflict of the 20th century brings into light the difference in their geographies. China’s position in the region is compared with that of Germany prior to World War 1 that was a land power while China aims at becoming a sea power. The writer foresees a similarity of China’s ambitions in the South China Sea with that of the US Caribbean adventure when it kept the British out of the region, by implementing Monroe doctrine that helped it to become a world power. China thus aims at the US exit from the region and to become a Sea power in the Indian Ocean. However, the major difference between the Caribbean and the South China Sea for the author rests in the fact that the latter being home to the international shipping routes cannot be dominated by a single power.